2003
DOI: 10.1074/jbc.m302943200
|View full text |Cite
|
Sign up to set email alerts
|

Netrin Binds Discrete Subdomains of DCC and UNC5 and Mediates Interactions between DCC and Heparin

Abstract: Netrins are secreted proteins that elicit both attractive and repulsive responses in migrating cells in the central and peripheral nervous systems. Netrins interact with members of two distinct families of transmembrane receptors, represented by DCC (deleted in colorectal cancer) and UNC5. A human netrin fragment (soluble netrin; sNetrin) was purified from an engineered Chinese hamster ovary cell line and used in a pull-down assay to map the interactions between netrin and its receptors. We find that sNetrin b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
2
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(97 citation statements)
references
References 23 publications
4
89
2
2
Order By: Relevance
“…Deletion of FN3 through FN6 eliminates binding. FN5 has been previously implicated in netrin binding either directly or through an interaction mediated by heparin (Bennett et al, 1997;Geisbrecht et al, 2003). However, in our assay, deletion of FN5 does not abolish binding.…”
Section: Unc5c Requires the Second Ig Domain To Bind Netrincontrasting
confidence: 51%
“…Deletion of FN3 through FN6 eliminates binding. FN5 has been previously implicated in netrin binding either directly or through an interaction mediated by heparin (Bennett et al, 1997;Geisbrecht et al, 2003). However, in our assay, deletion of FN5 does not abolish binding.…”
Section: Unc5c Requires the Second Ig Domain To Bind Netrincontrasting
confidence: 51%
“…It was reported that a domain located in the N terminus of netrin-1 (the so-called laminin-VI domain) interacts with both DCC and UNC5H receptors [ Fig. 2B; (20)]. We show that a soluble extracellular domain of DCC (DCC-EC-Fc) is able to inhibit both DCC/netrin-1 and UNC5H2/netrin-1 interaction, as measured by ELISA (SI Fig.…”
Section: Resultsmentioning
confidence: 69%
“…We consequently produced a flagtagged fifth fibronectin type III domain of DCC, DCC-5Fbn, a domain located in the ectodomain of DCC that is known to interact with netrin-1 (20) (Fig. 2B Inset).…”
Section: Resultsmentioning
confidence: 99%
“…However, the large size (1100 aa) of the complete extracellular domain of DCC may complicate its use in vivo. An alternative could be to use shorter polypeptides, corresponding to the fourth or fifth fibronectin-like domain of DCC (Fitamant et al, 2008;Delloye-Bourgeois et al, 2009a, b), which are both known to interact with netrin-1 (Geisbrecht et al, 2003). Unlike the complete ectodomain, the fifth and fourth fibronectin-like domains do not counteract interaction between netrin-1 and its receptors, but rather block receptor multimerization (Mille et al, 2009a).…”
Section: Drs As New Therapeutic Targetsmentioning
confidence: 99%